THE INFLUENCE OF REGIONAL GOVERNMENT (PEMDA) CHARACTERISTICS ON AUDIT OPINION WITH REGIONAL GOVERNMENT (PEMDA) FINANCIAL PERFORMANCE AS A MEDIATION VARIABLE: Empirical Study of Regency/City Governments in Banten Province 2018 - 2021 - Alfarisi, Inzaghi Fakhrij; Taqi, Muhamad; Susanto, Denny (Review of Accounting and Taxation, 2024)
Purpose - With local government financial performance serving as a mediating variable, this study intends to investigate the impact of local government characteristics, whose indicators are the degree of reliance and audit results on audit opinions Design/methodology/approach - The Regency/City Government in Banten Province from 2018 to 2021 serves as the study's population. In this investigation, 8 samples were evaluated using the saturation sampling technique. The financial reports of each PEMDA, whose information was collected from the Banten Province Representative Office of the Financial Audit Board (BPK), served as the source of the data for this study. Logistic regression analysis and mediation regression analysis were the analytical techniques employed in this investigation Finding - The outcomes of this study suggest that the amount of reliance and audit findings have a favorable effect on audit opinion, but that this effect is stronger when measured using financial performance as a mediating variable. Originality -   Paper Type – Research Paper   Keywords: Dependency Level, Audit Findings, Audit Opinion, Local Government Financial Performance